A little rendezvous in Bali - Wan Mohamad, Wan Srihani; Nangkula, Utaberta (Fakulti Rekabentuk dan Senibina, Universiti Putra Malaysia, 2014)
We would like to present, with great pleasure a travelogue that illustrates and record every single moment in the magical Island of Bali through a combined effort of our 3rd year students. The travelogue expresses every single participant's thoughts, feelings and experiences. It is structured in such a way that each day is presented through their SEE, FOOD and PLAY sections. These colourful photos and sketches are just a fraction of what the whole of us experienced. We have described with the simplest of words to make others feel what we felt, to make others see what we saw even to make others taste what we tasted when we were there